Ordered-disordered domain coexistence in ternary lipid monolayers activates sphingomyelinase by clearing ceramide from the active phase - Ale, Elisa Carmen (2012)
We explored the action of sphingomyelinase (SMase) on ternary monolayers containing phosphatidylcholine, sphingomyelin (SM) and dihydrocholesterol, which varied along a single tie line of phase coexistence. SMase activity exhibited a higher rate and extent of hydrolysis when the film is within the liquid-expanded (LE)/liquid-ordered (LO) coexistence range, compared to monolayers in the full LO phase. Since Alexa-SMase preferably adsorbs to the LE phase and there was no direct correlation found between enzymatic activity and domain borders, we postulate that the LE phase is the active phase for ceramide (Cer) generation. The enzymatically generated Cer was organized in different ways depending on the initial LE/LO ratio. The action of SMase in Chol-poor monolayers led to the formation of Cer-enriched domains, while in Chol-rich monolayers it resulted in the incorporation of Cer in the LO phase and the formation of new Chol- and Cer-enriched domains. The following novel mechanism is proposed to provide an explanation for the favored action of SMase on interfaces that exhibit an LE-LO phase coexistence: the LO phase sequesters the product Cer causing its depletion from the more enzyme-susceptible LE phase, thus decreasing inhibition by the reaction product. Furthermore, LO domains function as a substrate reservoir by allowing a rapid exchange of the substrate from this phase to the SM-depleted LE phase.